(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Neutrophils are an important element of the microenvironment of a tumour. By secreting Vascular Endothelial Growth Factor (VEGF), which promotes angiogenesis, these cells contribute to the development and spread of the disease. Our study involving 294 female breast cancer patients demonstrated a significant increase in absolute neutrophil count as tumour size increased (ANC). By secreting VEGF, neutrophils promote angiogenesis and infiltrate neutrophil cells at the site of the tumour, hence augmenting the growth of the tumour. Our data indicate that the ANC influences the extent of lymph node metastasis in patients of diverse ages. Tumour Necrosis Factor (TNF), which is produced by neutrophils, enhances the migration of cancer cells, suggesting that neutrophils may play an essential role in the migration of cancer cells to lymph nodes. In addition, it has been observed that ageing might change the activity of neutrophils, making it a possible factor in the development of metastatic cancer. Thus, it is possible to conclude that neutrophils may contribute to the development and spread of cancer. In addition, it may be hypothesised that if cancer patients' treatments reduce neutrophil numbers, this may reduce the risk of proliferation of cancer cells and metastasis and improve their clinical outcomes. To discover the underlying mechanisms by which neutrophils promote tumour growth and improve prognosis, additional study on absolute neutrophil count is required.